Activity of Mikania micrantha leaf extract against subterranian termite and wood decay - Yuliati Indrayani; Alkhadi Alkhadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
Mikania micrantha is a wild weed that thrives in tropical areas, grows rapidly in areas with high humidity and light intensity as well as in fertile soil. Meanwhile, Indonesia's tropical climate is also a suitable habitat for the breeding of termites and wood decay fungi. This study aims to determine the bioactivity of M. micrantha leaf extract against subterranean termite, Coptotermes curvignathus (Holmgren) and wood decaying fungus, Schizopyllum commune and its optimal extract concentration to prevent termite attack and inhibit fungal growth. The extracts were obtained by drying and mashing of M. micrantha leaves. The leaf powder was sieved with a 40-60 mesh filter and macerated with methanol for 3x24 h. The maceration results were filtered and the filtrate was concentrated using a rotary evaporator. Furthermore, identification of the secondary metabolites of the extract was carried out by phytochemistry. The bioactivity test included anti-subterranean termite and wood decay fungus using Potatos Dextrose Agar (PDA) medium. The results showed that M. micrantha leaf extract affected sample weight loss, termite mortality rates and the growth of wood decay fungi. Furthermore, the concentration of M. micrantha extract was inversely proportional to the sample weight loss and directly proportional to the termite mortality rate. In addition, the concentration of M. micrantha leaf extract had a negative correlation with the growth of the decaying fungus of S. commune therefore, the concentration of the extract was directly proportional to the growth inhibition of fungus. Meanwhile, the 4% extract concentration led to the increase in termite mortality rate above 80% and inhibited fungal growth by 100%. The results suggest that the bio-efficacy data from this study may be used to develop wood protecting systems based on wild weeds which are found in tropical areas.